Study of Nasakh-Mansukh in the Interpretation of the Verses of War and Peace in the Book of Tafsir Imam Al-Qurthubi - Mutma’innah, Nur’izzatul; Isnaeni, Ahmad (Westscience Press, 2025)
The Qur'an is a guideline for Muslims that contains various laws and teachings that must be understood through interpretation. One of the important concepts in the science of tafsir is Nasakh-Mansukh, which is the abolition or change of laws in certain verses. This study examines how Imam Al-Qurthubi interprets the verses of war and peace in the context of Nasakh-Mansukh. Using qualitative methods, based on historical-sociological analysis, as well as thematic and hermeneutic approaches, this study found that Imam al-Qurthubi affirmed that the message of peace in the Qur'an remains relevant despite the verses that discuss war. He does not necessarily consider the verse of war to remove the verse of peace, but understands the two types of verse in the context of different applications. The results of this study are expected to provide new insights in understanding the relationship between war and peace verses and their interpretation implications in contemporary life.